The Epoxy Group of Pramanicin Is Required for the Optimal Endothelium-Dependent Relaxation of Rat Aorta - Chiu-Yin Kwan; Wen-Bo Zhang; Joanna Miller; Paul H.M. Harrison; Salina Kassan; David Liscombe (Elsevier, 2003)
The vascular effects of a newly discovered anti-fungal agent, pramanicin (PMC), and its two analogues, PMC-A, in which the epoxy group is replaced by a - HC = CH - bond, and PMC-B, on which the diene is converted to the saturated (CH2)4-derivative, respectively, were investigated in rat aorta. All three compounds caused an initial endothelial-dependent relaxation, which is prevented either by removal of endothelium or inclusion of the nitric oxide synthase inhibitor L-NAME. Upon prolonged incubation with the aortic rings, they also caused endothelial cell dysfunction characterized as reduced relaxation to carbachol (CCh). These effects were the strongest for PMC, being completely inhibitory at 20 μM after 30 min incubation, whereas those of PMC-A and PMC-B were smaller and comparable with each other, causing 30 - 40% inhibition at 20 μM. PMC and its analogues had no effect on KCl-induced contraction and also had no effect on relaxation induced by sodium nitroprusside, suggesting that these compounds had no effect on the basic mechanisms of the contractile elements. Phenylephrine (PE)-induced contraction, however, was significantly reduced in the presence of these compounds, the inhibitory effect being strongest with PMC, but this inhibitory action was rapidly reversible and not of the competitive mode with respect to PE. We conclude that the epoxy group in PMC is required for the optimal vascular effects. We have discussed and speculated upon the possible mechanisms of action of PMC. The potent, selective, and irreversible inhibitory effect of PMC on the endothelial function points to its potential development into an anti-angiogenic drug.